Millennial-scale erosion rates in the Harz Mountains (Germany) from cosmogenic 10Be: implications for landscape evolution of basement highs in Central Europe - R. Hetzel; H. Rother; R. Wolff; K. Hölzer (Eiszeitalter und Gegenwart, 2024)
Understanding how landscapes evolve under changing tectonic and climatic boundary conditions requires the quantification of erosion rates on different temporal and spatial scales. Here we present results of local and catchment-wide erosion rates derived from in situ-produced cosmogenic 10Be for the Harz Mountains – a typical basement high in Central Europe that was uplifted by reverse faulting during the Late Cretaceous inversion of the Central European Basin. The summit region of the Harz (Brocken peak at 1141 m a.s.l.) is formed by Permian granite and surrounded by an Oligocene low-relief surface that was carved into Palaeozoic metasediments. This planation surface lies at an elevation of 500–700 m a.s.l. and stands ∼ 300 m above the lowlands surrounding the Harz Mountains. Our 10Be erosion rates, derived for granitic catchments with a size of 0.3–24 km2, are slope-dependent and range from 24 ± 2 to 55 ± 3 mm kyr−1. We find that catchments situated within the low-relief surface with mean slope angles < 10° erode at rates of 24–30 mm kyr−1​​​​​​​, whereas catchments characterized by larger portions with steeper slopes (i.e. 20 to 35°) upstream and downstream of the low-relief surface erode at higher rates of 30–55 mm kyr−1. Local bedrock outcrops on the planation surface erode at lower rates of around ∼ 20 mm kyr−1. Taken together, our 10Be data document and quantify the slope-dependent erosion of the Harz topography at a rate of a few tens of metres per million years and the denudation and lowering of the Tertiary Harz planation surface and its progressive incision by rivers. The observed difference between (higher) rates of erosion affecting soil-covered surfaces compared to the (lower) rates of erosion on exposed bedrock surfaces suggests that the topographic relief within the Harz is still growing at a mean rate of approximately 5–10 mm kyr−1. Considering our data in the context of the existing but contradictory conceptual models on the evolution of the Harz topography, we suggest that the post-Oligocene elevation difference of ∼ 300 m between the planation surface and the lowlands around the Harz is the result of three different processes: first, mountain uplift due to a potential reactivation of the range-bounding reverse fault during the Neogene and Quaternary until ∼ 0.5 Ma; second, moderate erosion of weak sedimentary rocks in the regions surrounding the Harz Mountains; and third, localized lowering of areas in the vicinity of the Harz by dissolution and lateral migration of Permian salt at depth. Finally, we note that active reverse faulting along the northern boundary of the Harz Mountains is not compatible with the available geological, geophysical, and geodetic data.